Pseudocohnilembus longisetus, a hymenostome ciliate from Antarctica - Thompson, Jesse C. (W&M ScholarWorks, 1964)
In December 1961, Dr. Stanley Wilson, of the Virginia Institute of Marine Science, collected some unidentified plant material from an exposed rock surface at an elevation of about 100 feet on Nelly Island, an island situated 12 miles west-northwest of Wilkes Station, Antarctica. This frozen collection was later received by the author and cultures were made from it in November 1962. A small ciliate was isolated from the material; subsequent studies of both living and silver impregnated animals identified it as a member of the genus Pseudocohnilembus ( Evans and Thompson, 1964).